The 52 and 60 kD Ro/SS-A : antigens where are they? : do anti-Ro/SS-A autoantibodies cause cutaneous disease? - Yell, Jennifer Anne (Division of Dermatology, 2017)
Systemic lupus erythematosus, considered a multifactorial autoimmune disease, is a disease affecting many systems, with associated immunological abnormalities. It has a striking diversity of clinical patterns, pathologies and prognoses. Genetic factors determine the inherited baseline, on which environmental, hormonal and infectious triggers act to produce autoantibodies. Ro antibodies have been considered pathogenic in subacute cutaneous and neonatal lupus erythematosus. I affinity-purified antibodies to the 52 kD Ro from immunised rabbits (whole 52 kD protein) and human sera (using two immunodominant regions of the protein). I affinity-purified antibodies to the 60 kD Ro from immunised rabbits (whole 60 kD protein) and human sera (using two immunodominant regions of the protein, as well as the total "native" protein). Using these purified antibodies, with immunofluorescence on normal neonatal human keratinocytes, I showed that the 52 kD Ro is mainly cytoplasmic and the 60 kD Ro is mostly nuclear, with some fine cytoplasmic staining. I looked at the capacity of these purified antibodies to penetrate living keratinocytes under various conditions (hormones, drugs and vitamins). No antibody penetration was found, although one whole serum gave low levels of intracellular fluorescence. I studied the putative membrane translocation of 52 kD and 60 kD Ro under conditions of stress (UV A or UVB with or without hormones, drugs, vitamins and heat shock). I could not identify translocation of the 52 or 60 kD antigens with purified antibodies, although some whole sera showed fluorescence. I can find no evidence that antibodies directed against the 52 and 60 kD Ro antigens cause cutaneous disease.